Uplift capacity of enlarged base piles in sand - Niroumand, Hamed (Electronic Journal of Geotechnical Engineering, 2012)
Pile foundations, also known as substructure, are used to carry and transfer the load of the structure to the bearing ground located at some depth below ground surface. The main components of the foundation are the pile cap and the piles. Piles are long and slender members which transfer the load through the shallow soil of lower bearing capacity to deeper soil or rock of high bearing capacity. They are also used in normal soil condition to resist uplift forces or in poor soil condition to resist lateral forces. Most of the piles are made from three main types of material which are wood, steel and concrete. Piles are normally driven, drilled or jacked into the ground and connected to pile caps. Based on a few number of laboratory model results many investigators reported the uplift response of piles in cohesionless soil, a review of related previous works shows that not much research has been done to define the uplift capacity in cohesionless soil, a problem that is often encountered in field. The paper observed that the ultimate uplift capacity is dependent on the relative undrained/drained shear strength of cohesionless soil, the depth ratio of embedment and soil thickness ratio. © 2012 ejge.